Comparison of neoadjuvant immunotherapy versus routine neoadjuvant therapy for patients with locally advanced esophageal cancer: A systematic review and meta-analysis - Qin, Hao; Liu, Futao; Zhang, Yaozhong; Liang, Yuxiang; Mi, Yuan; Yu, Fan; Xu, Haidi; Li, Kuankuan; Lin, Chenxi; Li, Lei; Tian, Ziqiang; Wang, Lei (Frontiers in Immunology, 2023)
Background: The neoadjuvant use of immune checkpoint inhibitor combined with chemotherapy (nICT) or chemoradiotherapy (nICRT) in locally advanced esophageal cancer (EC) is currently an area of active ongoing research. Therefore, we carried out a comprehensive meta-analysis to compare the efficacy and safety of the new strategy with routine neoadjuvant strategy, which included neoadjuvant chemotherapy (nCT) and neoadjuvant chemoradiotherapy (nCRT). Patients and methods: MEDLINE (via PubMed), Embase (via OVID), ISI Web of Science database and Cochrane Library were included. And, all of them were searched for eligible studies between January, 2000 and February, 2023. The pathological complete response (pCR) and major pathological response (MPR) were primary outcome of our study. The second outcome of interest was R0 resection rate. Odds ratio (OR) and associated 95% CI were used as the effect indicators comparing the safety and efficiency of the neoadjuvant immunotherapy with the routine neoadjuvant therapy. Fixed-effect model (Inverse Variance) or random-effect model (Mantel-Haenszel method) was performed depending on the statistically heterogeneity. Results: There were eight trials with 652 patients were included in our meta-analysis. The estimated pCR rate was higher in the neoadjuvant immunotherapy group (OR =1.86; 95% CI, 1.25–2.75; I2=32.8%, P=0.166). The different results were found in the esophageal squamous cell carcinoma (ESCC) and esophageal adenocarcinoma (EAC) subgroups, the estimated OR was 2.35 (95%CI, 1.00–2.72; I2=30.9%, P=0.215) in the EAC subgroup, and 2.35 (95% CI, 1.20–4.54; I2=45.3%, P=0.161) in the ESCC subgroup, respectively. The neoadjuvant immunotherapy also showed the advantage in the MPR rates (OR =2.66; 95% CI, 1.69–4.19; I2=24.3%, P=0.252). There was no obvious difference between the neoadjuvant immunotherapy and routine neoadjuvant therapy with respect to surgical resection rate, R0 resection rate, surgical delay rate; while more treatment-related adverse events were observed for the neoadjuvant immunotherapy for pneumonitis/pneumonia (OR=3.46, 95% CI, 1.31–9.16; I2=67.3%, P=0.005) and thyroid dysfunction (OR=4.69, 95% CI, 1.53–14.36; I2=56.5%, P=0.032). Conclusion: The pooled correlations indicated that the neoadjuvant immunotherapy (both nICT and nICRT) could significantly increase the rates of pCR and MPR, compared with routine neoadjuvant therapy (both nCT and nCRT) in the treatment of locally advanced EC.